Integrating organic fertilization and soil tillage techniques to enhance the nutritional attributes of “Royal” grapes (Vitis vinifera L. cv.) - Ozkan Kaya; Fadime Ates; Selda Daler; Nurhan Keskin; Metin Turan (Food and Energy Security, 2024)
Abstract In the context of global efforts to improve food quality against the backdrop of climate change and increasing demands for food, this study sought to investigate the influence of tillage and fertilization methods on essential nutritional components. Thus, this extensive investigation into the variability of organic acid, sugar, and vitamin content within berries over the years 2020 to 2022 shows the critical influence of agricultural practices on the nutritional quality of grape. Our findings revealed significant fluctuations in the levels of various organic acids, with oxalic and propionic acids seeing a notable increase in 2022, while tartaric, citric, and maleic acids decreased. Similarly, a significant rise in sucrose, glucose, and fructose levels was documented by 2022, alongside a variable trend in vitamin content. The PCA results revealed a clear impact of tillage and organic amendments on the biochemical composition of Royal grapes. Heatmap findings confirmed the results obtained from PCA and showed that certain treatments resulted in high organic acid content, while others resulted in high sugar content. However, disc harrow and olive blackwater 2021 followed by disc harrow and Antep radish 2021 and no‐tillage broccoli 2020 were the best treatments with a balanced distribution of organic acids, soluble sugars, and vitamins among all treatments. On the other hand, chisel and olive blackwater '20 was the treatment with the lowest ratio of organic acids, sugars, and vitamins, followed by chisel and Antep radish 2020. These results show that the concentration of organic acids, soluble sugars, and vitamins in grapes is more affected by the tillage method than the type of organic fertilizer used. To sum up, our study holds valuable implications for viticulture and agriculture at large, highlighting the potential to tailor farming practices for enhanced nutritional outcomes. Such advancements not only promise to elevate the quality of agricultural produce but also contribute to the broader objective of achieving food security and nutritional adequacy, thus offering a roadmap for future research and practice in sustainable agriculture and viticulture.